An investigation of the challenges faced by women-owned small-medium enterprises in the Makhado Local Municipality, Limpopo Province - Netshikhudini, Mulalo (My University, 2023)
For decades, business has been a male-dominated activity, but recently, a considerable number of female entrepreneurs have emerged around the world. One of the factors that motivate women to become entrepreneurs is the flexibility offered by self-employment. Self-employment allows people to better manage their work-life. However, there are challenges experienced by women entrepreneurs in growing their businesses. These challenges may be due to the fact that women have a wide range of responsibilities both at work and at home that affect their productivity. Multiple family tasks and responsibilities for women entrepreneurs may cause work-family conflict, which could jeopardise their long-term business success. Therefore, the objective of this study was to look into the difficulties faced by women-owned small businesses in the province of Limpopo's Makhado Local Municipality. In this study, a thematic data analysis approach was applied. Qualitative in nature and approach, the study relied on face-to-face interviews to collect the data. It was found that most women start small enterprises because they are compelled by outside forces such as unemployment and poverty. Furthermore, qualification and experience play an important part in operating a business. The findings also indicate that women-owned small medium enterprises do not get any financial support, training from the government or private sector. Hence, they rely more on their family for any support. Women who own small-medium enterprises also encounter discrimination in various forms, including being told that they ought to remain at home and take care of the family mainly because they are women. The study recommends that financial assistance, training, women networking, infrastructure, awareness campaigns and implementations of legislation meant to assist women-owned small-medium enterprises should be prioritised.
Thesis (MBA.) -- University of Limpopo, 2023
Keywords: Entrepreneurship; Theory of planned behaviour; Women-business owners; Qualitative methods; Small Medium & Micro Enterprises; Women-owned business enterprises; Businesswomen; Small business -- South Africa -- Limpopo; Women-owned business enterprises -- South Africa -- Limpopo; Entrepreneurship -- South Africa -- Limpopo